Teacher Agency in Ghanaian Schools: Impact of Career Choice Motivations and Perceptions of the Teaching Profession - Francis Adams; Qiong Li; Hu Mu (Behavioral Sciences, 2025)
This study explored teacher agency and its impact on the motivation and perceptions of the teaching profession. This study employed a cross-sectional survey design, in which questionnaires were administered to a sample of 574 basic school teachers in Ghana. Structural equation modeling (SEM), a multivariate statistical technique for analyzing complex relationships among latent constructs, was employed to examine the direct, indirect, and moderated effects among the study variables, thereby ensuring accurate and reliable results. This study found that the motivation and perception factors have a strong positive impact on teacher agency. The moderator analysis showed that intrinsic career value was a significant predictor of teacher agency for both male and female teachers. The results also indicated the significant moderating effect of age on the relationship between intrinsic career value and teacher agency. Additionally, the findings revealed that perception factors partially mediate the relationship between motivation factors and teacher agency. However, this study is limited by its cross-sectional design and focus on public basic school teachers in Ghana, suggesting the need for future research to include longitudinal approaches, broader geographic representation, and private school contexts. Finally, the theoretical and practical implications are addressed.